The influences of fashion on the design of fabrics and fashion at the time of contemporary social transformations (Al-Academy, 2023)
The design of fabrics and fashion is manifested by aesthetic advantages betting with the movement of society in its quest to develop as an independent art in itself that is linked to the values and aesthetic concepts of other arts and what appears in them of intellectual systems calling for renewal and modernity. Which brought about a wide change in public taste, as well as a desire for innovation . Which made fashion an interesting aesthetic phenomenon and taste is always subject to change constantly to comply with the social variables that occur in human life, as the fashion that appears in a certain era of time and takes a great distance from spreading as something new and out of the ordinary is in fact the fruit of the development of fashion design Today, it is subject to many studies in the aesthetic, historical and social structure . The design of fabrics and fashion, and became an independent art in appearance and influencing the recipients, which is a topic worthy of research. Hence the importance of research in the aesthetic necessities of the subject. Fashion and its impact on the development of textile and fashion design, raising the level of taste among the recipients, and deepening the level of aesthetic perception of theories and concepts related to fashion . he research aims to reveal the influences of fashion on the design of fabrics and fashion in a time that witnessed many social transformations, and the research identifies spatially in the role of fashion design in the world and temporally from 2019 to 2023. The second topic dealt with the influences of fashion in the time of contemporary social transformations. As for the third chapter, the researcher followed the analytical descriptive approach to analyze the fashion models selected from the international fashion houses and analyzed them. Designing textiles, fashion, and fashion, as one complements the other